ANALISA DAYA POROS MESIN BERPENGGERAK UDARA BERTEKANAN DENGAN VARIASI BERAT FLYWHEEL - Farid, Ahmad (Politeknik Harapan Bersama Tegal, 2022)
One of the technological developments in energy engineering is the processing and utilization of energy, both from renewable and non-renewable energy. The innovation that inspired the experiment in this research was to engineer a pressurized air-driven machine by analyzing the weight gain of the flywheel on the power of a pressurized air-driven engine. The purpose of this study is to determine the size of the flywheel weight that can produce the highest pressurized air-driven engine power and also to know the value of the engine shaft rotation for each flywheel weight size. The benefits of this research are expected to contribute ideas to research on the development of compressed air driven machines to make them even more perfect. The method of testing and research carried out is an experimental method, namely by testing variations in flywheel weight from 2.5 kg, 3.5 kg, 4.5 kg, 5.5 kg and 6.5 kg and at air pressure in the tube 100Psi, 60Psi and 25Psi with a load on the engine shaft of 5 kg. The results of testing the flywheel load setting 2.5kg-6.5kg air-driven engine experienced a decrease in the engine shaft rotation from 1185rpm - 322.67rpm so that the engine shaft power also decreased from 7.17 HP at a flywheel weight of 2.5kg; 100Psi to 1.95 HP on a 6.5kg flywheel; 25Psi. This shows that the engine's ability to increase power is by minimizing the flywheel load at 25Psi and also required air pressure of 100Psi on the compressor tube to be able to drive the engine optimally.